The Use of Twitter by Government: Engaging the Secure Based Feeling on Economic Investment - Wira Yudha Alam; Siti Istikhoroh; Teguh Dwi Putranto (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2023)
Indonesia witnessed a very rapid growth of 12.58 per cent in the tourism sector in 2018, compared with an average world growth of only 5.6 per cent, as well as an ASEAN growth of 7 per cent. To make tourism become one of the most important sectors for Indonesia in terms of increasing government revenue and improving the efficiency and competitiveness of citizens on international markets. Of course, a lot needs to be prepared to achieve this goal. One of them is a safe community-based feeling. Because Indonesia is currently developing and requires significant domestic investment, security in Indonesia is a focus that needs to be improved. And in order to be able to understand a sense of community security, the government must have a relationship between the government and the community. This study aims to know e-government service quality implementation by the Ministry of Agrarian Affairs and Spatial Planning via twitter. The method used in this study is a content analysis of Twitter posts from the Ministry of Agrarian Affairs and Spatial Planning of the Republic of Indonesia for a period of 1 year, from 1 January 2019 to 31 December 2019. Based on the findings and discussion, it is concluded that secure based feeling towards investment can be achieved through social media, one of which is Twitter by providing a more understanding related to land rights or land that will be used in investment.